2022
DOI: 10.1016/j.jsxm.2022.05.144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Differences in Problematic Pornography Use: Considerations for Gender and Sexual Orientation

Abstract: Background While preliminary research suggests non-heterosexual men and women view more pornography than their heterosexual counterparts, few studies have examined how problematic use differs across sexual and gender identity groups. Aim We sought to test measurement invariance across popular measures of problematic pornography use (PPU) and examine mean PPU differences across heterosexual men, non-heterosexual men, heterosex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…failures to stop/control one's pornography use) and craving [39, 40]. Prior exploratory and confirmatory analyses support a single‐factor solution, and MI testing suggested that the BPS is able to meaningfully compare gender‐ and sexually‐diverse groups [40–43]. Previous research on the BPS has shown acceptable psychometric indicators for reliability and validity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…failures to stop/control one's pornography use) and craving [39, 40]. Prior exploratory and confirmatory analyses support a single‐factor solution, and MI testing suggested that the BPS is able to meaningfully compare gender‐ and sexually‐diverse groups [40–43]. Previous research on the BPS has shown acceptable psychometric indicators for reliability and validity (i.e.…”
Section: Introductionmentioning
confidence: 99%